2021
DOI: 10.3389/fped.2021.705553
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Index Is Associated With Early Prognosis of Surgical Treatment for Tetralogy of Fallot

Abstract: Objectives: To evaluate the predictive value of the pulmonary vein index (PVI) in the early prognosis of patients who received total tetralogy of Fallot (TOF) repair.Methods: We retrospectively reviewed 286 patients who underwent TOF repair in our institution between July 2013 and May 2020. The PVI, McGoon ratio, and Nakata index were measured and calculated. Logistic regression, linear stepwise regression, receiver operating characteristic (ROC) curve analysis, and Cox proportional hazards modeling were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In their study, Yuan et al indicated that a reduced PVI is a significant risk factor for early death and prolonged postoperative recovery. They estimated the cutoff point of PVI at 300.3 mm 2 /m 2 12 . In our case, the PVI was 368.12 mm 2 /m 2 , which resulted in an uneventful postoperative recovery.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In their study, Yuan et al indicated that a reduced PVI is a significant risk factor for early death and prolonged postoperative recovery. They estimated the cutoff point of PVI at 300.3 mm 2 /m 2 12 . In our case, the PVI was 368.12 mm 2 /m 2 , which resulted in an uneventful postoperative recovery.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we evaluated the predictive value of PVI for the determination of early postoperative outcomes among patients with TOF. A reduced PVI is a significant risk factor for both early mortality and prolonged postoperative recovery 12 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations